2020
DOI: 10.3390/molecules25245861
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Free Energy Profiles of Enantioselective Organocatalytic Aldol Reactions under Full Solvent Influence

Abstract: We present a computational study on the enantioselectivity of organocatalytic proline-catalyzed aldol reactions between aldehydes in dimethylformamide (DMF). To explore the free energy surface of the reaction, we apply two-dimensional metadynamics on top of ab initio molecular dynamics (AIMD) simulations with explicit solvent description on the DFT level of theory. We avoid unwanted side reactions by utilizing our newly developed hybrid AIMD (HyAIMD) simulation scheme, which adds a simple force field to the AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 97 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Ab Initio molecular dynamics (AIMD) simulations have been carried out using the ORCA MD module written by Brehm and collaborators. [54][55][56] Newton's equations of motion have been solved through numeric integration using the velocity Verlet algorithm within the Canonical Ensemble with time steps of 0.5 and 1.0 fs. The simulations have been accomplished using the Berendsen's thermostat at temperatures of 673, 473, and 573 K for bare Cu 5 -Cu 5 , circumpyrene-supported Cu 5 -(O 2 ) 4 , and circumpyrene-supported Cu 5 -Cu 5 , respectively.…”
Section: Ab Initio Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Ab Initio molecular dynamics (AIMD) simulations have been carried out using the ORCA MD module written by Brehm and collaborators. [54][55][56] Newton's equations of motion have been solved through numeric integration using the velocity Verlet algorithm within the Canonical Ensemble with time steps of 0.5 and 1.0 fs. The simulations have been accomplished using the Berendsen's thermostat at temperatures of 673, 473, and 573 K for bare Cu 5 -Cu 5 , circumpyrene-supported Cu 5 -(O 2 ) 4 , and circumpyrene-supported Cu 5 -Cu 5 , respectively.…”
Section: Ab Initio Molecular Dynamics Simulationsmentioning
confidence: 99%
“…However, numerous studies have demonstrated that the dielectric constants of mixed solvents do not combine linearly with those of pure solvents. , In explicit solvent models, solvent molecules are treated explicitly, and the free energy is typically evaluated by analyzing the trajectory of time evolution of phase space obtained via MC simulations or molecular dynamics (MD) . Since this approach can provide more molecular details, ab initio MD (AIMD) , and mixed QM/MM methods , have been extensively applied to get insight into solvent effects on the chemical reaction. For example, Mellmer et al demonstrated that tuning the concentration of hydroxyl groups in aqueous organic solvent mixtures by the AIMD method can greatly increase the rate of various acid-catalyzed reactions by up to 1000-fold.…”
Section: Introductionmentioning
confidence: 99%
“…The spring constant value for NEB calculations was set to 0.02 au. In some cases, the minimum energy path has been quantified using free energy surfaces [54] using well‐tempered metadynamics. The additional parameter that requires well‐tempered metadynamics (polarization temperature) was set to 15000 K. This value proved to be adequate to overcome energy barriers of approximately 30.0 kcal mol −1 .…”
Section: Introductionmentioning
confidence: 99%